Respon Model Gedung Beton Bertulang dengan Penambahan Dinding Pengisi terhadap Beban Gempa - Syamsi, Muhammad Ibnu (Semesta Teknika, 2018)
Earthquake-resistant building structures designs usually are not considering the influence of non-structural walls. In fact, non-structural walls could give additional strength for building especially to help retaining seismic loads. The Influence of masonry walls on infill frame building structure model to the open frame model became the objective in this study. Spectrum response and time history are applied to both types of model to know and compare the behavior of those two samples. The observed building is an educational facility and located in an area prone to earthquakes. The parameters used in this research are based on natural periods, shear forces, and drift ratios. After performing linear analysis, the drift ratio on each floor of the building could be categorized as safe condition because it has not exceeded its limit. Structural models with masonry walls have larger stiffness than open frames. Moreover, the greater structure stiffness in the infill frame model is able to narrow the drifts that occur from the inter-story drift ratio to be smaller. Due to higher stiffness, the base shear results from structures with infill frame system models are also larger than structures modeled with open frames system.